Nuevo ligando con acción alostérica sobre el receptor nicotínico de Torpedo californica - Paván, Carlos Humberto (2019)
The nicotinic acetylcholine receptor belongs to a superfamily of ion channel receptors\ntriggered by ligand, also known as cystine-loop receptors. It is widely distributed in\nnature; in mammalian the neuronal subtype is present at the cholinergic synapses of the\nperipheral and central nervous systems whereas muscle subtype is located at the\nneuromuscular junction. Alterations in nicotinic receptor subtypes cause a variety of\npathologies in humans: myasthenia gravis, Alzheimer's disease, certain types of epilepsy,\netc. Currently, there are no drugs which are allosteric modulators of the receptor and\nused in therapeutics.\nIn this work we studied its interaction with a ligand called AC4-ASA, with properties\nof allosteric modulator of the nicotinic receptor, in order to establish its binding\ndeterminants. We used the photo-affinity labeling strategy, followed by a mass\nspectrometry study.\nAC4-ASA binds to two sites at the ?/? interface, one site in ?/? and two other sites\nlocated on the ? subunit. We propose binding models for the interaction sites with the\nreceptor, as well as a possible mechanism of modulation of receptor affinity for nicotine.